Peningkatan Pengetahuan Teknik Menyusui Pasien Post Sectio Caesarea Di Rsu Assalam Gemolong - Purnama, Elmi; , Sulastri, S.Kp., M.Kes (2016)
Breastfeeding can increase nutrient intake and give a lot of love that is useful for the development of babies. Exclusive breastfeeding can be given for 6 months and continued until the age of 2 years to get the optimal result for the baby's development. According to WHO, AAP, AAFP and IDAI, recommends exclusive breastfeeding for 6 months and continued up to two years to deliver results both for the mother, the baby and for the mother's workplace. Purpose: The purpose of nursing care is to improve patients knowledge about breastfeeding or breastfeeding technique is good and right in order to get satisfaction of patients and infants during breastfeeding. Methods: Scientific paper was prepared using the descriptive method or by the case study approach is the scientific method to the nature of data collection, analyze the data and draw conclusions from the existing data. The preparation of this scientific paper taking a case or a patient at the General Hospital ward Assalam Gemolong Sragen Namiroh 1 and assessment on March 29, 2016. The process of collecting data by studying the medical record, interview the patient, perform a physical examination, observe and make study documentation using a journal or book related. Results: The results of the above goals 3x24 hours after the act can be concluded that the patient already knows about the technique of breastfeeding or breast-feeding is good and right through health education given.